3D dynamic simulation and visualization for GIS based infiltration excess overland flow modelling - Ujang, Muhamad Uznir (Springer Berlin / Heidelberg, 2008)
A key prerequisite for effective GIS based Infiltration Excess Overland Flow (IEOF) simulation and visualization is good knowledge of GIS core concept and prediction of soil infiltration rates due to impervious area coverage. The success or failure for a GIS based IEOF simulation and visualization resides initially with the georeference system used. Implementation of soft geo-objects representing flow elements such as streams, mudflows and runoff provides better dynamic visualization in terms of velocity and direction.Inclusion of volume would offer substantial effort towards determining volume of stormwater runoff hits the flood-plain areas, estimating channel flow capacity, routing and diversions to reduce flood disasters realistically. However, cartographers have long complained about the poor quality of the output from GIS, which generally today is not due to limitation of the GIS itself, but to lack of understanding of cartographic principles among hydrologists and environmentalists.With rapid growth of urbanization, industrialization and climate change, previous historical runoff and infiltration rate would provide improper guide for the future enhanced visualization of the current 2D land use surface to improve future hydrologic impact assessment. This study aims to visualize the influence of georeferencing towards IEOF simulation represented by volumetric soft geo-objects dynamically within 3D environment driven by physically based Green-Ampt method. Visualization is analyzed by focusing on infiltration and overland flow process using conformal Malaysian Rectified Skew Orthomorphic (MRSO) and equidistance Cassini-Soldner projections. Appropriate usage of georeferencing system to visualize 3D dynamic IEOF simulation may obtain high demands from civil engineers, environmentalists, town planners, geologists and meteorologists as base for producing scientific results of flood management control, sustainability for long-term development purposes, stream restoration,rehabilitation and hydrologic impact assessment.